RICE SEED TREATMENTS BY SOAKING IN WATER AND THREE PESTICIDES (CARBOSULFAN, BENOMYL, AND IMIDACLOPRID) TO CONTROL FOLIAR NEMATODE Aphelenchoides besseyi - Miftahul Ajri; Siwi Indarti; Christanti Sumardiyono (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Aphelenchoides besseyi is one of the most important parasitic nematodes in rice plants, capable of dormancy in rice seeds. This study aims to determine the effects of soaking rice seeds in water and pesticides (carbosulfan, benomyl, and imidacloprid) on the mortality of A. besseyi, seed viability, and symptoms in rice seedlings. This study specifically used rice seeds infected with A. besseyi. Cold water treatment (cwt) at 5-10ËšC for 24 hours followed by hot water treatment (hwt) at 52ËšC for 10 minutes caused 51.17% A. besseyi mortality yet reduced the seed viability. Soaking the seed in the water at 25-30ËšC for 24 hours followed by hwt at 57ËšC for 10 minutes and hwt at 52ËšC for 10 minutes could cause 48.67%, 39.18% and 33.05% nematode mortality, respectively. Low nematode mortality in all treatments (less than 60%) showed symptoms of A. besseyi infection in rice seedlings 21 days after planting. Seed dressing with imidacloprid 5WP (2% by seed weight) caused 47.25% A. besseyi mortality, whereas benomyl 50WP (0.2% by seed weight) and carbosulfan 25ST (2% by seed weight) caused only 27.61% and 11.34%. Based on two parameters (nematode mortality and seed viability), the most effective treatments were soaking the rice seeds in the water at 25-30ËšC for 24 hours and seed dressing with imidacloprid.